2018
DOI: 10.1039/c7en00466d
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning provides predictive analysis into silver nanoparticle protein corona formation from physicochemical properties

Abstract: Proteins encountered in biological and environmental systems bind to engineered nanomaterials (ENMs) to form a protein corona (PC) that alters the surface chemistry, reactivity, and fate of the ENMs. Complexities such as the diversity of the PC and variation with ENM properties and reaction conditions make the PC population difficult to predict. Here, we support the development of predictive models for PC populations by relating biophysicochemical characteristics of proteins, ENMs, and solution conditions to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 38 publications
2
83
0
Order By: Relevance
“…(15,23) with robust tolerance of heterogeneity. However, the quantitative prediction of the functional compositions of the protein corona by a comprehensive understanding of complex NP-protein binding patterns remains unavailable using machine learning (24). To address these problems, the present work attempts to use a powerful RF model to identify the rules for protein corona formation by associating numerous NP physicochemical properties and distinct experimental conditions with quantitative protein corona compositions (e.g., hydrophily and function).…”
Section: Significancementioning
confidence: 99%
“…(15,23) with robust tolerance of heterogeneity. However, the quantitative prediction of the functional compositions of the protein corona by a comprehensive understanding of complex NP-protein binding patterns remains unavailable using machine learning (24). To address these problems, the present work attempts to use a powerful RF model to identify the rules for protein corona formation by associating numerous NP physicochemical properties and distinct experimental conditions with quantitative protein corona compositions (e.g., hydrophily and function).…”
Section: Significancementioning
confidence: 99%
“…ρ To identify potential links between the LFC and the physicochemical features, we fitted linear regression models using the LFC as a response variable and the physicochemical properties as covariates, for each NP size (for predictive models see Findlay et al [70] for example). Using a Bayesian factor analysis against all possible models (see Section 2.4) we observed that the best fitted model was the same for each NP size:…”
Section: S10 S30 S80mentioning
confidence: 99%
“…[44] Findlay et al tackled this important problem of predicting the protein corona around silver nanoparticles using an ML approach. [45] They training a random forest model using biophysicochemical characteristics of proteins, ENMs, and solution conditions. The area under the receiver operating characteristic curve was 0.83 indicating strong predictive performance.…”
Section: Identifying and Modeling The Biologically Relevant Entitymentioning
confidence: 99%